Pengaruh Motivasi Belajar Siswa Terhadap Pestasi Belajar PKN di Kelas V SDN 200201 Padangsidimpuan - Ahsan Ziyadi (Warta Pendidikan | e-Journal, 2021)
Motivation is one of the several things which determine the successful of the student learning activity. Without motivation, learning process is difficult to achieve optimum success. The use of the principle of motivation is something essential in the learning and education process. This article is thrilled to investigate the influence of learning motivation to the student civic education. This correlation descriptive study was conducted as a case study on elementary school fifth grade students and the objective was to describe the level of influence of student’s motivation toward civic education. Atotal of 26 fourth grade students at SDN 200201 Padangsidimpuan City are used as a sample. Data was collected using a questionnaire as an instrument of learning motivation variables and test results as the average student achievement variable. Results of data processed with statistical calculations and the average correlation performed using SPSS 16.0. Results showed that on average, learning motivation and science learning performance of students achieve good interpretation. The Influence of student’s learning motivation showed significant high correlation and donate the influence of 48.1% on student’s civic education.